COMMUNICATION AND LANGUAGE, IDEOLOGY, AND POWER IN PRESIDENT PRABOWO SUBIANTO’S STATE SPEECH 2025 - Muhammad Hasyimsyah Batubara; Cut Dara Ilfa Rahila (IAIN Surakarta, 2026)
This study investigates how language represents ideology and power in President Prabowo Subianto’s 2025 state speech delivered before the Annual Session of the Republic of Indonesia’s MPR/DPR/DPD. Using a qualitative approach with Critical Discourse Analysis (CDA) based on Fairclough’s three-dimensional model and van Dijk’s socio-cognitive framework, the study examines textual structures, discursive practices, and social practices within the speech. The results reveal that the linguistic composition of the speech exhibits a strong ideological bias toward nationalism, economic sovereignty, and social justice. Historical references, metaphors, religious language, and populist expressions served as rhetorical tools, combining to create a rhetorical arsenal that crafted legitimacy and closeness to the people. The speech positions corruption, economic dependency, and serakahnomics as common enemies while promoting UUD 1945 as the foundation of political and economic ideology. This study contributes to understanding Indonesian political discourse by showing how language functions to legitimize power, shape public perception, and construct national identity. The study found that political language in modern Indonesia blends technocratic, populist, religious, and historical discourse into hegemony. It is suggested that more research be conducted on Indonesian presidential speeches.